Modelo de gestión social para el logro del buen vivir en la Corporación Fortaleza del Valle de la ciudad de Calceta - Saltos Alcívar, María Guadalupe (2024)
Management systems are the basis for the development of correct administration, the objective of this study was to structure a strategic model of social management to achieve Good Living in the associates of the Fortaleza del Valle Corporation, the applied methodology consisted in the execution of a field, referential and descriptive study, considering the implementation of three phases where, in the first instance, the diagnosis of the state of the variables social management and good living was carried out, to reference the need to develop the model, then carried out its construction by reviewing academic bibliographic sources, which allowed establishing the components of the social management model, to consequently describe the elements incorporated in each of the developed stages. Regarding the results of the study, the absence of adequate planning is observed where social integration programs are executed informally and without a correct allocation of budget or programming, which allows us to conclude that the organization studied does not present a formal system to demonstrate the results of its social execution activities and how these influences the good living of its associates and collaborators.